PROCEDIMIENTOS PARA LA EVALUACIÓN INTEGRADORA DEL PROCESO DOCENTE EDUCATIVO FÍSICO EN LA SECUNDARIA BÁSICA: PROCEDURES FOR THE INTEGRATIVE EVALUATION IN THE PHYSIC TEACHING-LEARNING PROCESS - Jeffers Duarte, Bernardo (Opuntia Brava, 2018)
En el artículo se tratan elementos que propician la regulación progresiva de las cargas y la evaluación integradora del proceso docente educativo físico en la Secundaria Básica, los cuales consisten en la modelación de los contenidos en correspondencia con la potencia que generan las cargas externas, basado en requisitos didácticos, los indicadores para evaluar y regular las cargas y los procedimientos que incluye el software para establecer la dinámica de la regulación y evaluación durante el desarrollo de este proceso. ABSTRACT The article deals with elements that guarantee the progressive regulation of charges and the integrative evaluation in the physics teaching-learning process in junior high school, which consists of the modeling of the contents in correspondence with the potency that generates the external charges, based on didactic requirements, the indicators to evaluate and to regulate charges and the procedures that the software includes for establishing the dynamic of the regulation and evaluation during this process. KEY WORDS: evaluation, integrative evaluation, teaching-learning process